A Review on Wave Energy Harvesting Technologies - Alaaddin Yılmazer; https://orcid.org/0000-0002-2838-6887 (Gazi Üniversitesi Fen Bilimleri Dergisi)
With the rapid development of technology, the demand for electrical energy is increasing every year. Although electrical energy is a very clean form of energy in its direct use, the use of fossil fuels in the production process causes environmental problems. In this context, renewable energy sources are of critical importance in terms of clean and sustainable energy production. Wave energy stands out as a relatively under-researched topic in this field. Our country, which is surrounded by sea on three sides and has an inland sea, needs to invest more in wave energy and support more studies in this field. This study analyses the historical development of wave energy and aims to provide a perspective for future research.